Russians on the Polish Labour Market - Gomółka, Krystyna Ewa (Review of European and Comparative Law, 2020)
The article looks into the employment of Russian citizens in Poland in 2004–2018. It presents the legal basis for Russians’ entering Poland and taking up work without having to seek a work permit, and specifies who must apply for such a permit. Russian citizens can obtain refugee status under the Geneva Convention, which grants them the right to move freely, choose their place of residence and undertake paid employment, while guaranteeing social security. On the basis of the Act on granting protection to aliens, citizens of the Russian Federation may obtain subsidiary protection if their return to their country of origin may expose them to a real risk of serious harm. A tolerated stay is granted to aliens where an alien might be expelled to a country in which their life, freedom and personal security would be jeopardised, where they could be subjected to torture, degrading treatment, humiliation, forced to work or deprived of the right to a fair trial. Training and employment can be undertaken in Poland under the bilateral agreements between Poland and Russia: the Treaty on friendly and good-neighbourly cooperation and the Cooperation Agreement in the fields of science, culture and education. In Poland, the entry and stay of foreign nationals is governed by the Act on aliens, their education by the Higher Education Act, whereas the employment of foreigners is regulated by the Act on employment promotion and labour market institutions. The empirical basis of the study was provided by the analysis of data from the Polish Ministry of Family, Labour and Social Policy and the Demographic Yearbook. Russians constitute the third largest group (after Ukrainians and Belarusians) of the post-Soviet States’ citizens coming to Poland. The analysis conducted showed that employment in Poland was chiefly sought by the citizens of the Russian Federation who arrived in Poland for a limited period and for permanent residence. In 2004, the Russians represented 4.4% and in 2018 – 0,66% of all foreigners who received work permits in Poland. Before 2015 some Russian nationals took up work in Poland as the managers of their own companies. Since 2015, there has been an influx of workers from Russia in three occupational groups: IT specialists, skilled workers and workers in elementary occupations. Most of the Russians were employed in the wholesale and retail, information and communication, construction, transport and warehousing sectors, which were the same sectors where Polish entrepreneurs reported demand for Russian workers. The demand significantly exceeded the number of Russians employed.